Micronuclei in cytokinesis-blocked lymphocytes of patients following iodine-131 radiotherapy - Kašuba, Vilena (Radiology and oncology (Ljubljana), 1999)
The micronucleus assay in cytochalasin-B cytokinesis blocked peripheral blood lymphocytes in 10 patients with hyperthyreosis and various types of thyroidal carcinomas was investigated. Patients receivcd 259-5180 MBq I-131 sodium iodide perorally. Micronucleus (MN) frequencies were measured before and afterI-131 administration. Pre treatment MN results were regarded as controls.Our results show considerable variability concerning age and activityapplied. Also, the number of MN and the number of binucleated cells with micronuclei (BNMN) showed Poisson regression adjust for within subject correlation overdispersion. Log dose alone was not significant. The interaction of time and dose was significant at higher doses, while the rate of MN changing was slower. Relative risk time was calculated for the lowest dose (259 MBq). By doubling the dose, the rate of daily increase in the numberof MN and BNMN decreases by approximately 5% (Relative risk MN=0.955; Relative riskBNMN= 0.954).
Keywords: Adverse effects; Cytochalasin b; Hyperthyroidism; Iodine radioisotopes; Lymphocytes; Micronucleus tests; Radiotherapy; Therapeutic use; Thyroid neoplasms